Optimalisasi Pemanfaatan Lahan Kosong Melalui Penanaman Toga (Tanaman Obat Keluarga) Di SDN 31 Mataram - Isna Zuriatni; Intan Permata Hati; Mauliana Gusfian; Nanda Nur Sabrina; Mahesa Zanuba Putri (Educational Consultant & Counseling Career (EC3) Mataram, 2025)
This research was motivated by the utilization of vacant land at SDN 31 Mataram which was previously not used to plant Family Medicinal Plants (TOGA). The aim is to increase students' knowledge and awareness of herbal plants through a TOGA planting program in the school environment. This activity was carried out as part of the Teaching Assistance program for the 2024/2025 academic year using land observation methods, socialization of the benefits of TOGA using presentation media, and practice of planting and caring for plants by students. The types of plants chosen included ginger, turmeric, lemongrass, aloe vera, and rosella flowers because their health benefits are easy for children to understand. The results showed that vacant land was successfully utilized as a TOGA area, students responded positively to the socialization, and were actively involved in planting and routine maintenance in turns. This program not only introduces traditional medicine but also fosters responsibility and concern for the environment. Therefore, similar activities are recommended for other schools as contextual learning as well as efforts to optimize land.